1992
DOI: 10.1103/physrevd.46.658
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational radiation in black-hole collisions at the speed of light. I. Perturbation treatment of the axisymmetric collision

Abstract: In this and the two following papers II and III we study the axisymmetric collision of two black holes at the speed of light, with a view to understanding the more realistic collision of two black holes with a large but finite incoming Lorentz factor y. The curved radiative region of the space-time, produced after the two incoming impulsive plane-fronted shock waves have collided, is treated using perturbation theory, following earlier work by Curtis and Chapman. The collision is viewed in a frame to which a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
232
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(252 citation statements)
references
References 19 publications
16
232
1
3
Order By: Relevance
“…The shockwave geometry can be analysed in terms of the four regions I, II, III and IV shown in figure 4. The geometry in regions I, II and III is actually flat whereas in region IV the collision curves the spacetime in a way which is difficult to analyse [33]. However, if we take the shockwaves to be particle shockwaves (having the same energy µ for simplicity) and the impact parameter such that Gµ/L 1, then we expect that the curvature in region IV will be small.…”
Section: A Consistent Analysismentioning
confidence: 99%
“…The shockwave geometry can be analysed in terms of the four regions I, II, III and IV shown in figure 4. The geometry in regions I, II and III is actually flat whereas in region IV the collision curves the spacetime in a way which is difficult to analyse [33]. However, if we take the shockwaves to be particle shockwaves (having the same energy µ for simplicity) and the impact parameter such that Gµ/L 1, then we expect that the curvature in region IV will be small.…”
Section: A Consistent Analysismentioning
confidence: 99%
“…Combining two shock waves, we can set up the high energy collision. This system was originally developed by D'Eath and Payne [4]. The black hole formation with an impact parameter for D = 4 was investigated by Eardley and Giddings [3], and they showed that the apparent horizon which encloses two particles exists at the instance of collision for sufficiently small impact parameter.…”
mentioning
confidence: 99%
“…Apart from [11], where gravitational bremsstrahlung of soft photons was studied in the context of string theory, the existing estimates of gravitational radiation either refer to phase (ii), or are based on the assumption of an already existing BH (e.g. radiation from particles falling into the BH [12]), on results of linearized theory relevant only to the case of non-gravitational scattering [8], on weakly relativistic numerical simulations [13] or again on collisions of waves in 4D [14]. For a related discussion see also [15].…”
mentioning
confidence: 99%